On the Drazin index of regular elements - Patrício, Pedro (2009)
It is known that the existence of the group inverse $a^#$ of a ring element $a$ is equivalent to the invertibility of $a^2a^-+1-aa^-$, independently of the choice of the von Neumann inverse $a^-$ of $a$. In this paper, we relate the Drazin index of $a$ with the Drazin index of $a^2a^-+1-aa^-$. We give an alternative characterization when considering matrices over an algebraically closed field. We close with some questions and remarks.